Quantitative analysis of phospholipids by 31P-NMR. - N Sotirhos; B Herslöf; L Kenne (Journal of Lipid Research, 1988)
High-field 31P nuclear magnetic resonance spectroscopy was used to quantitate phospholipids in mixtures in organic solvents. The sample is dissolved in chloroform-methanol and analyzed at 161.7 MHz with decoupling of the protons. Signals were identified using authentic compounds, and their relative distribution was measured in mole percent. The method has good accuracy and reproducibility, and was used to analyze phosphatidylcholine, phosphatidylethanolamine, sphingomyelin, lysophosphatidylcholine, lysophosphatidylethanolamine, phosphatidylinositol, cardiolipin, and phosphatidic acid in egg lecithin. Four commercial egg phospholipids and the phospholipids from a total lipid extract of rat liver were analyzed. The method could be utilized to analyze phospholipids from other sources.